Report on outcomes and get everyone involved: The Participatory Perfor mance Story Reporting Technique - Dart, J. (2008)
This paper outlines the background and philosophy of Collaborative Out comes Reporting (COR) and Performance Story Reporting (PSR), providing an overview of these emerging techniques and showing how they can be used as a framework for reporting on contribution to long-term outcome s (or targets) using mixed methods and participatory process. The repo rt serves as an introduction to these approaches in evaluation and dis cusses their bias, limitations and where they might best be applied.